EMPLOYEE PERFORMANCE EVALUATION AT THE NORTH GUNUNGSITOLI DISTRICT OFFICE GUNUNGSITOLI CITY - Yatatema Zega; Ayler Beniah Ndraha; Palindungan Lahagu; Odaligoziduhu Halawa (Jurnal Ilmiah METADATA, 2026)
This study aims to evaluate employee performance at the Gunungsitoli Utara Sub-district Office, Gunungsitoli City. The evaluation was conducted to determine the level of employee task implementation, factors influencing performance, and obstacles faced in carrying out public service responsibilities. The study used a qualitative approach with data collection techniques such as observation, in-depth interviews, and documentation. Research informants included the Sub-district Head, Sub-district Secretary, Head of General and Personnel Sub-division, employees, village heads, and the community as service users. The research results indicate that, in general, employees have performed their duties quite well, particularly in administrative services and coordination with villages. However, several problems remain, such as suboptimal discipline, lack of initiative, limited work facilities, and an imbalance between the workload and the number of employees. Factors influencing performance include motivation, leadership, the work environment, competence, and supporting infrastructure. The main obstacles faced are limited human resources, delays in coordination between departments, uneven understanding of tasks, and limited mastery of information technology. This study concludes that improving employee performance can be achieved through strengthening the performance evaluation system, providing ongoing training, improving work facilities, and consistently fostering discipline and motivation. The research recommendations are expected to assist the Gunungsitoli Utara Sub-district Office in improving the quality of public services to be more effective, responsive, and accountable.